The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1007/s10238-010-0095-4
|View full text |Cite
|
Sign up to set email alerts
|

VEGF expression and angiogenesis in oral squamous cell carcinoma: an immunohistochemical and morphometric study

Abstract: Angiogenesis is involved in tumor progression of oral squamous cell carcinoma (OSCC). In this study, we have investigated by immunohistochemistry vascular endothelial growth factor (VEGF) expression in tumor cells and we have correlated VEGF expression to microvessel area, evaluated by using CD105 as a marker of endothelial cells, in bioptic specimens of 54 human OSCC. Results demonstrated that VEGF is highly expressed in OSCC tumor specimens when compared to pre-neoplastic and normal tissues, without differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 30 publications
(56 reference statements)
8
44
0
2
Order By: Relevance
“…001), but it was not related to age, sex, tumor size and grade (p>0.05). in line with previous studies (24)(25)(26)(27) and verified that CD105 is expressed more in tumoral tissues and may have a major role in tumor development. We also observed a positive relation between CD105 expression and lymph node metastasis.…”
Section: Resultssupporting
confidence: 79%
“…001), but it was not related to age, sex, tumor size and grade (p>0.05). in line with previous studies (24)(25)(26)(27) and verified that CD105 is expressed more in tumoral tissues and may have a major role in tumor development. We also observed a positive relation between CD105 expression and lymph node metastasis.…”
Section: Resultssupporting
confidence: 79%
“…Comparison of the mean area using the Bonferroni multiple comparison test showed significant differences between the AOSMF and WDSCC groups, but not among any of the other groups. Though no previous studies have compared OSMF and WDSCC, a few studies have demonstrated a significant increase of MVD in WDSCC relative to normal oral mucosa (21,22). …”
Section: Discussionmentioning
confidence: 99%
“…Consistently, a recent study by Mărgăritescu et al had similar findings with VEGF expression being reduced in poorly differentiated oral squamous cell carcinoma compared to moderate and well differentiated forms. 36 Moreover, VEGF expression at the invading tumor front was 4-10 times higher than in the deep tumor areas and was significantly associated with poor prognosis, particularly within stage I endometrial disease. 37 Another study by Toyoki et al showed that VEGF and COX-2 expressions decreased with tumor dedifferentiation.…”
Section: Discussionmentioning
confidence: 95%